Relationship Between Patient Satisfaction and Dimensions of Health Service Quality with Revisit Interest of Outpatient in Lumajang Health Center - Mirawati; Yunita Armiyanti; Anisah Ardiana (STIKes Patria Husada Blitar, 2024)
High outpatient revisit interest reflects good health services that meet patient expectations. However, in Lumajang, 25 health centers experienced a decline in outpatient revisit numbers. This study aimed to examine the relationship between patient satisfaction and dimensions of service quality with outpatient revisit interest at Lumajang Health Center. Using a cross-sectional design, the study involved 386 outpatients selected through purposive sampling. Inclusion criteria included health centers with a decline of over 200 visits, patients aged 15-50 years, literate, spiritually healthy, and visiting for the first time between December 2023 and February 2024. Exclusion criteria were severe illness or mental disorders hindering questionnaire completion. Data were collected through direct questionnaires and analyzed using chi-square tests. Results showed that 90.4% of patients were satisfied with health services. Service quality dimensions scored as follows: tangibility (91.2%), reliability (60%), responsiveness (93.8%), health insurance (95.6%), and empathy (87.8%). The chi-square analysis revealed a significant relationship between responsiveness and revisit interest (p=0.034). However, no significant relationship was found between revisit interest and satisfaction, tangibility, reliability, health insurance, or empathy (p>0.05). In conclusion, while most patients expressed satisfaction with the services provided, the key factor influencing revisit interest was the responsiveness of health workers. This highlights the importance of responsive healthcare in fostering patient loyalty and improving outpatient revisit rates.